2023
DOI: 10.1002/pip.3672
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing intermediate band solar cell performances through quantum engineering of dot states by droplet epitaxy

Abstract: We report the effect of the quantum dot aspect ratio on the sub‐gap absorption properties of GaAs/AlGaAs quantum dot intermediate band solar cells. We have grown AlGaAs solar cells containing GaAs quantum dots made by droplet epitaxy. This technique allows the realization of strain‐free nanostructures with lattice matched materials, enabling the possibility to tune the size, shape, and aspect ratio to engineer the optical and electrical properties of devices. Intermediate band solar cells have been grown with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…They reported a high open circuit voltage, super-linearly increasing with the concentration factor, which might be a signature of IB operation. More recently, Scaccabarozzi et al, have reported in [6] GaAs/AlGaAs QD solar cells grown by droplet epitaxy, where they designed QDs with different aspect ratios to tune the GS confinement energy and interlevel spacing aiming at suppressing thermal extraction of photogenerated carriers toward the barrier states. Notably, they reported the lowest open circuit voltage penalty, with respect to the reference bulk cell, for the sample with largest energy separation between the 0-D states and largest GS confinement.…”
Section: Toward Ib Operation: Competition Between Thermal and Optical...mentioning
confidence: 99%
See 1 more Smart Citation
“…They reported a high open circuit voltage, super-linearly increasing with the concentration factor, which might be a signature of IB operation. More recently, Scaccabarozzi et al, have reported in [6] GaAs/AlGaAs QD solar cells grown by droplet epitaxy, where they designed QDs with different aspect ratios to tune the GS confinement energy and interlevel spacing aiming at suppressing thermal extraction of photogenerated carriers toward the barrier states. Notably, they reported the lowest open circuit voltage penalty, with respect to the reference bulk cell, for the sample with largest energy separation between the 0-D states and largest GS confinement.…”
Section: Toward Ib Operation: Competition Between Thermal and Optical...mentioning
confidence: 99%
“…This is the regime in which reported devices usually fall [3], [4]. On the other hand, demonstrating devices operating under a truly intermediate band regime remains an open challenge and still requires extensive work on design and fabrication of appropriate QD materials and devices [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…To that end, it is imperative that there is a null density of states (DOS) connecting the IB to the VB and the CB. , If a high DOS exists between the IB and, for example, the CB (Figure b), the IB ↔ CB thermal excitation and relaxation of carriers will be too fast, effectively reducing the cell’s voltage. This has been the case in the IBSCs investigated so far, in which cryogenic temperatures were required to mitigate the thermal coupling of the IB to the VB or the CB. , In contrast, if a band diagram was achieved in which the IB is effectively isolated from both the VB and the CB (Figure c), the energy split between bands would be too high for thermal processes to take place even at room temperature (RT), leaving optical processes as the main coupling mechanism; first requisite for very-high-efficiency IBSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, low-energy photons can contribute to increasing the photocurrent by promoting electrons from the VB to the CB via sequential two-photon absorption (TPA), using the IB as a steppingstone (see red and yellow transitions in Figure a). Even though the generation of additional photocurrent due to TPA has been demonstrated in different IB materials, this process has been proven inefficient so far, mainly because of a too weak photon absorption for transitions involving the IB. ,, As a consequence, no IBSC prototype has yet demonstrated an increase in efficiency assignable to the required IB properties.…”
Section: Introductionmentioning
confidence: 99%